A fete worse than death eaudiobook - Bishop, Claudia (Hemlock Falls Mystery, 2013)
Sisters Meg and Sarah Quilliam make sure guests feel right at home when they visit the Inn at Hemlock Falls. Located in upstate New York, Hemlock Falls is a small town renowned for its scenic beauty—and scenes of crime. Disaster strikes a mere week before the Hemlock Falls Ladies' Auxiliary hosts the annual Spring Fete when the festival's chairwoman—the redoubtable Adela Henry—gives up her job in a huff. Who's going to judge the justly renowned Jell-O architecture contest? Who will stop the members of the Craft Guild from sabotaging their rivals, the Crafty Ladies? More to the point, who's got the tact, diplomacy, and iron will necessary to organize the booths and settle quarrels over the programming? Hemlock's mayor hopes to assure the fete's success when he recruits professional organizer Linda Connally and her staff to take over Adela's duties. But when Connally's body turns up in the trunk of a used car at Peterson's Automotive, Meg and Sarah are back in the detecting business.